Integration of spiritual intelligence in modern tools for creativity and innovative thinking using theory of inventive problem solving (TRIZ) - Rohana, Hamzah; Abdul Rashid, Aziz; Imaduddin, Abidin; Haslinda @ Robita, Hashim; Nur Qistina, Abdullah (Universiti Malaysia Pahang, 2019)
The development of creativity and innovation is needed in preparing today’s generations to face challenges in their future. However, the main focus in creativity and innovation development process is on cognitive, affective, imagination and practises (psychomotor) that allow total freedom for individual to present their product. In fact, unfortunately this will make them losing their own direction. Therefore, this article tries to integrate between the development of creativity and innovation with spiritual element, which the vital component and the main guidance for decision making in any innovation process. Indeed, this spiritual element is closely related with one of the basic concepts in Theory of Inventive Problem Solving, (TRIZ) which is ideality. TRIZ has been introduced in Universiti Malaysia Pahang (UMP) since 2017 where this theory proposed four basic concepts in inventive problem solving. The concept of ideality opens up an opportunity for researcher to integrate and prove that the concept is related with the element of spirituality. By inculcate the spiritual element in innovative process, this will eventually lead to the development of spiritual intelligence of God-consciousness, which is one of the core value in UMP. It is also a basic principle to guide our young generation about the real meaning of freedom and at the same time it acts as a main value in developing students’ soft skills. What’s important, this value also will give a good direction in innovation and educate our students to make more effective decision in problem solving process as what is emphasized in this article.